EVALUASI IMPLEMENTASI PRA-OTORISASI PENGGUNAAN ANTIBIOTIK KELOMPOK AWARE DENGAN PROGRAM PENGENDALIAN RESISTENSI ANTIMIKROBA (PPRA) PADA PASIEN RAWAT INAP DI RSUP DR.SARDJITO - Bintang Hasby Nuraida; Endang Setyowati; Emma Jayanti Besan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Antibiotics are used to treat infections caused by bacteria and are classified as prescription medications; however, irrational and unwise use of antibiotics still frequently occurs, both in primary healthcare facilities and hospitals. The prevalence of antibiotic use in Indonesia is considered high, around 40-60%. The aim of this study is to evaluate the implementation of pre-authorization for the use of Aware group antibiotics within the antimicrobial resistance control program (PPRA) in inpatient patients at Dr. Sardjito General Hospital. This research uses an observational (non-experimental) retrospective design, taken from inpatient medical record data at Dr. Sardjito General Hospital during the period October 2022 to March 2023. The sample size in this study was 200 people, calculated using the Slovin formula. The data analysis method used in this study is comparative descriptive analysis. The results of this study show that from ages 0-18 years, the majority were aged 0-4 years at 66.5%. By gender, females accounted for 40.5% and males 59.5%. Antibiotic use before pre-authorization was 63% and after pre-authorization 37%. The category of antibiotic use according to the AwaRe group in this study consisted of the Access group 802, Watch 924, and Reserve 126. After the implementation of pre-authorization, antibiotic use changed to Access 386, Watch 568, and Reserve 125. In this study, the most used antibiotic according to the Defined Daily Dose (DDD) method was azithromycin at 73.3. Meanwhile, antibiotics with the lowest Defined Daily Dose (DDD)/100 patient days were erythromycin at 0.01 and co-amoxiclav at 0.02.